The Concept of Family Education in The Perspective of Al-Qur`an and Hadist - Febriani, Evi; Kumaidi, Muhamad; Kartika, Ely (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Family education is part of national education. This is stated in the National Education System law. Family education is the first and primary environment of Islamic education. This study seeks to explore various views on family education through literature studies (Library Research), Furthermore, the main ideas are explored with descriptive analytical patterns, then a blue print is presented in the corridor. The result is known that family education is a continuous and continuous guidance process. Some meanings of family according to the Koran related to the meaning of family include 'Al-A'ilah, 'Ahlun/Ahl,'Al-Qurba, 'Arhamun, 'Asyiroh. Surah at-Tahrim 66 verse 6 is a solid foundation for family education. The methods applied include discipline, exemplary, advice, habituation, execution and reward. The material/curriculum of family education includes creed education, worship education, Akhaqul Karimah education, reading the Koran and the value of Islamic teachings. The purpose of family education is to convey the basis of ethical education, produce good morals, prepare for the next life, namely the afterlife. Furthermore, endeavoring and trying to meet daily needs and maintaining the value dimension of goodness, fostering the spirit of demanding knowledge, and encouraging professionals. The function of family education is to foster Solidarity, Education as well as Social Control.